A Case of Rapidly Progressive Diabetic Nephropathy Induced by Osimertinib - Kazunori Karasawa; Ken-ichi Akiyama; Taro Akihisa; Yoei Miyabe; Kosaku Nitta; Junichi Hoshino (Case Reports in Nephrology and Dialysis, 2023)
The number of patients with diabetic nephropathy is increasing worldwide and it is important to understand the underlying pathological mechanisms of the disease. In early stage diabetic nephropathy, the hyperglycemic environment leads to vascular endothelial cell damage, resulting in overexpression of vascular endothelial growth factor (VEGF) in podocytes and renal pathology of glomerular hypertrophy, glomerular basement membrane thickening, and mesangial hyperplasia. In diabetic nephropathy, renal thrombotic microangiopathy (TMA) develops and the nephropathy progressively worsens in some cases of severe glomerular podocyte damage. Further, receptor tyrosine kinase inhibitors (RTKIs) may suppress VEGF secretion via VEGF receptor-2 tyrosine kinase inhibition in podocytes, which results in renal TMA and rapid deterioration of diabetic nephropathy. Osimertinib, a third-generation irreversible epidermal growth factor receptor (EGFR)-TKI, is approved as a first-line treatment agent for metastatic or locally advanced EGFR mutation-positive non-small cell lung cancer. We encountered a case of a patient with diabetic nephropathy with lung adenocarcinoma treated with osimertinib, whose condition deteriorated from early nephropathy to end-stage renal disease in approximately 4 months. The patient had early diabetic nephropathy, but the use of a RTKI suppressed VEGF expression in podocytes, resulting in the induction of renal TMA and the development of rapidly progressive diabetic nephropathy.